FUZZY PROCEDURE FOR CALCULATING DAMAGE FROM RISKS ATTACHMENT AT AVIATION ACTIVITY BASED ON THE MODEL OF SELECTING OPTIMAL STRATEGIES - Kharchenko, Volodymyr; Alexeiev, Oleh; Pechevystyi, Ruslan (Proceedings of National Aviation University, 2019)
Safety management – is the main managerial function, which should be considered at a level that is at least adequate in importance to other functions of any airline, whose implementation should be based on a balanced allocation of resources to production tasks and means of protection, to contribute to the establishment of security space. When considering aspects of FS adopted the postulate that absolute, security does not exist. The essence of the postulate is that after the adoption of protective measures residual risk always remains, which is considered as a measure of probability, as well as the severity of harm to the safe functioning of the system and the environment. Damage – is defined as physical damage or harm associated with the deterioration of a person’s health or vital functions, which reduces his or her ability to function normally in terms of physiology. Damage can be caused both directly, and indirectly and qualitatively classified by levels as catastrophic, critical, marginal, insignificant.